Help-Seeking Patterns Among LGBTQ Young Adults Exposed to Intimate Partner Violence Victimization. Issue 17 (September 2021) - Scheer, Jillian R.; Baams, Laura
Although intimate partner violence (IPV) is highly prevalent among lesbian, gay, bisexual, transgender, and queer (LGBTQ) young adults, only little is known regarding gender identity disparities in this population. Furthermore, virtually no research has examined IPV-related help-seeking patterns among LGBTQ young adults, including whether there are gender identity disparities in these rates and whether specific services are most likely to be used by LGBTQ young adults across IPV type. Participants were 354 LGBTQ young adults (ages: 18-25, 33.6% transgender and gender nonconforming [TGNC]) who experienced IPV victimization during their lifetime. TGNC young adults experienced more identity abuse victimization and reported 2.06 times the odds of seeking medical services, 2.15 times the odds of seeking support services, and 1.66 times the odds of seeking mental health services compared to cisgender sexual minority young adults. LGBTQ young adults with physical abuse victimization reported 2.63 times the odds of seeking mental health services, 2.93 times the odds of seeking medical care, and 2.40 times the odds of seeking support services compared to LGBTQ young adults without physical abuse victimization. Finally, LGBTQ young adults with identity abuse reported 2.08 times the odds of seeking mental health services and 2.58 times the odds of seeking support services compared to LGBTQ young adults without identity abuse. These findings provide a more complete understanding of gender identity as both risk and protective factors for IPV and IPV-related help-seeking. This study also provides implications for training providers, service availability, and resource allocation for LGBTQ young adults with IPV victimization.